Simulators, graphic - Klein, C. A., author; Maciejewski, Anthony A., author; John Wiley & Sons, Inc., publisher (Colorado State University. Libraries, 1988)
There are many situations in which a computer simulation with a graphic display can be very useful in the design of a robotic system. First of all, when a robot is planned for an industrial application, there are many commercially available arms that can be selected. A graphics-based simulation would allow the manufacturing engineer to evaluate alternative choices quickly and easily. The engineer can also use such a simulation tool to design interactively the workcell in which the robot operates and integrate the robot with other systems, such as part feeders and conveyors with which it must closely work. Even before the workcell is assembled or the arm first arrives, the engineer can optimize the placement of the robot with respect to the fixtures it must reach and ensure that the arm is not blocked by supports. By being able to evaluate workcell designs off-line and away from the factory floor, changes can be made without hindering factory production and thus the net productivity of the design effort can be increased.